Dynamic stability enhancement with fuzzy based power system stabilizer tuned by hottest non-traditional optimization technique - Linda, M Mary; Nair, N Kesavan (2010 International Conference on Computing, Communication and Networking Technologies, 2010)
The supplementary control signal is provided by means of Power System Stabilizer (PSS), will damp the low frequency oscillations. This paper presents the design of fuzzy logic based power system stabilizers using genetic algorithms in multimachine power system. In the proposed fuzzy expert system, generator speed deviation and its derivative are chosen as input signals to fuzzy logic based power system stabilizer. In this approach centers of membership functions and the parameters of the fuzzy logic controllers has been tuned using genetic algorithm. Inclusion of GA in tuning fuzzy logic based power system stabilizer will provide good damping and significantly reduces computational time in the design process. Simulation results on multimachine system subjected to small perturbation and three phase fault show the effectiveness and robustness of the proposed PSS over a wide range of operating conditions and system configurations. The problem of optimizing the membership functions and the parameters of fuzzy logic based power system stabilizer is converted into an optimization problem and which is solved by genetic algorithm with the integral of squared time squared error (ISTSE) based objective function.